2013
DOI: 10.1200/jco.2012.45.1096
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Determinants of Tumor Recurrence in Stage II Colon Cancer: Validation Study of the 12-Gene Recurrence Score in Cancer and Leukemia Group B (CALGB) 9581

Abstract: The 12-gene RS predicts recurrence in stage II colon cancer in CALGB 9581. This is consistent with the importance of stromal response and cell cycle gene expression in colon tumor recurrence. RS appears to be most discerning for patients with T3 MMR-I tumors, although markers such as grade and lymphovascular invasion did not add value in this subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(107 citation statements)
references
References 40 publications
3
102
0
2
Order By: Relevance
“…AORs for the intermediate (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and high (>30) scores were 4 and 19, respectively. The adoption of the test is associated with a trend for decrease in chemotherapy recommendations by clinicians.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…AORs for the intermediate (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and high (>30) scores were 4 and 19, respectively. The adoption of the test is associated with a trend for decrease in chemotherapy recommendations by clinicians.…”
Section: Discussionmentioning
confidence: 97%
“…The RS assay results were classified into low (<18), intermediate (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and high risk (≥31). 4 In order to further evaluate the effect of cutoff point of 25 proposed by the RxPONDER trial on chemotherapy decision, the intermediate scores of 18 to 30 were further classified into categories of 18 to 25 and 26 to 30.…”
Section: Data Source and Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although using slightly different Recurrence Score (RS) cut points than initially defined in QUASAR, the Venook and colleagues validation study of the 12-gene RS in CALGB 9581 confirmed the risk discrimination of Oncotype Dx in stage II patients (risk ranged 9%-26%; ref. 30). On the basis of a different prognostic assay, Kennedy and colleagues (29) reported that the 634-probes signature used in the ColDx test (Almac Diagnostics) also had the ability to discriminate risk of recurrence in patients with stage II colon cancer (HR ¼ 2.53; P ¼ 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…During the last few years, gene signatures have been developed from FFPE tumor samples to identify patients with stage II colon cancer who are at higher risk of disease recurrence (28)(29)(30)(31)(32). The study by Gray and colleagues (28) was designed as a validation study based on prospectively specified retrospective analyses of the QUASAR (QUick And Simple And Reliable) trial.…”
Section: Discussionmentioning
confidence: 99%